Canada's "New main street": The Trans-Canada Highway as idea and reality, 1912-1956. - Monaghan, David W. (University of Ottawa (Canada), 1997)
The purpose of this thesis is two-fold. First it examines the development of the concept of a Trans-Canada Highway from the early 1900's to 1940. Its roots can be traced to the significant increase in motor vehicle use, and the gathering momentum that characterized automobile technology in the 20th century. While the early development of the technology relied upon the promotional activities of automotive enthusiasts, the state was by no means oblivious to the potential benefits of automotive technology. Provincial governments in Canada contributed to the momentum through the provision of improved roads. Indeed, without publically funded roads, the new technology would have bogged down both literally and metaphorically The thesis outlines the technological momentum that characterized developments in highway technology and standards in the face of rising traffic volumes and the role of highway bureaucracies in promoting and sustaining the growth of the technology. It also explores how road networks allowed provincial governments to expand their own influence and, through user fees and gasoline taxes, to increase substantially their revenue base. By the 1920s automobile revenues comprised the major source of provincial revenues in Canada due to both domestic demand and a burgeoning tourist trade based upon motor travel. Secondly, the thesis examines why the federal government became involved in the construction of a great national road. This was by no means a foregone conclusion since the Canadian constitution effectively excluded the federal government from the provincial demesne of highway and road development. Nevertheless, by 1919 Ottawa was providing funding to the provinces for the development of a national highway system. While most provinces were eager to accept financial assistance for an increasingly expensive highway system, Ottawa remained uneasy in its role as a highway financier. This thesis will show that from the 1920s through the early 1950s the primary interest of the federal government in the Trans-Canada Highway was as a weapon against unemployment, the government's interest in the road waxing and waning with the business cycle. Ottawa's decision to embark upon the project in 1949-1950 was essentially driven by its concerns over rising unemployment and as a form of public investment designed to help counteract a projected downturn in the Canadian economy. However, once it had committed it self to the construction of a first rate, hard-surfaced highway in 1949, Ottawa was no longer content to simply fund the project but established the minimum standards and the route to be followed by the Trans-Canada Highway. With this higher level of involvement, the prestige of the federal Liberals then became associated with the Highway and its primary goal was the completion of a national highway.
Keywords: History, Canadian.